Molecular detection of blaCTX-M gene to predict phenotypic cephalosporin resistance and clinical outcome of Escherichia coli bloodstream infections in Vietnam - Son, Trinh Van; Manh, Nguyen Dang; Trung, Ngo Tat; Quyen, Dao Thanh; Meyer, Christian G.; Phuong, Nguyen Thi Kim; Hoan, Phan Quoc; Sang, Vu Viet; Nurjadi, Dennis; Velavan, Thirumalaisamy P.; Bang, Mai Hong; Song, Le Huu (Annals of clinical microbiology and antimicrobials, 2021)
Blood stream infections (BSI) caused by Extended Spectrum Beta-Lactamases (ESBLs) producing Enterobacteriaceae is a clinical challenge leading to high mortality, especially in developing countries. In this study, we sought to describe the epidemiology of ESBL-producing Escherichia coli strains isolated from Vietnamese individuals with BSI, to investigate the concordance of genotypic-phenotypic resistance, and clinical outcome of ESBL E. coli BSI.
Im Text ist "CTX-M" tiefgestellt
Gesehen am 04.11.2021